Perbedaan Manifestasi Klinis Kejang Demam Pada Anak Anemia dengan Tanpa Anemia di RSPAL dr. Ramelan Surabaya Tahun 2019-2022 - -, Delia (Surabaya Biomedical Journal, 2023)
Study aims: Febrile seizures are the most common neurological disorder in children. The incidence of febrile seizures is related to the incidence of epilepsy at 2-4% in the future and the probability of recurrence is about 30% and 50% after the first and second febrile seizures, respectively. Several recent studies have suggested that febrile seizures are more common in children with anemia. Anemia patients who experience febrile seizures can cause more severe clinical manifestations. Where 40.5% of the incidence of anemia in Indonesia occurs in children under the age of 5 years. Therefore, this study is conducted to determine the differences of the clinical manifestations of febrile seizures with and without anemia in children at RSPAL Dr. Ramelan Surabaya on 2019-2022. Methods: This study was an observational analytic study with a cross-sectional study approach and qualitative methods from secondary medical record data of infants and children aged 6 months-5 years at RSPAL Dr. Ramelan Surabaya for the period May 2019-May 2022. The number of samples in this study was 82 samples. Results: The characteristics of the sample which experiences the most febrile seizures occurres between the ages of 6-18 months, the gender of male with a temperature >38°C and manifestations in the form of simple febrile seizures. In addition, the results of the fisher exact test with a significance level of 5% shows p = 0.96 which means there is no difference in the clinical manifestations of febrile seizures in anemic and non-anemic children. Conclusion: The conclusion of this study is that based on the classification of febrile seizures, the most common clinical manifestations that occur in children with anemia and without anemia are simple febrile seizures. So that there is no difference in the clinical manifestations of febrile seizures in anemic children and without anemia.